School Heads Leadership and Attributes and Teachers’ Morale: Its Impication to School Performance - Buenvinida, Lerma P.; Tamayo, Rea G. (Advances in Social Sciences Research Journal, 2020)
This study determined the relationship among the school heads’ leadership and attributes, teachers’ morale and implication to school performance. Respondents of the study were 68 school heads and 532 teachers from public elementary schools of the Division of Laguna. The Level of Teacher’s Morale in terms of Teacher Rapport with Principal scored as good; while in terms of Satisfaction with Teaching was found moderately satisfied. Further, the relationship between school head leadership and professional attributes and teacher’s Morale in terms of rapport and personal and professional attributes are evident using the Chi-Square Test of Independence. The correlation between Building High Performance Team scores and Teacher Morale in terms of rapport comes out to be highly significant. However, School Leadership in terms of Problem Solving and Coordinating with Others and Leading & Managing Changes were not significant. For Interpersonal Sensitivity of School Heads and Teacher Morale in terms of rapport, the correlation is significant at p<.05. There are significant relationships between leading and managing changes to cohort survival, interpersonal sensitivity and completion rate with p<.05; and relationship between Teacher’s Morale in terms of satisfaction to completion rate. School heads need to evaluate and monitor the training needs assessment to address teachers’ professional growth and assist in improvement of the school performance. A similar research can be conducted to determine the validity of the relationship between teacher’s morale and school performance and to verify the results of this study.